I am working on my thesis on revenue management. I have been over the following problem multiple times now, but I fail to see where my mistake is. This example is based on The Theory and Practice of Revenue Management by Talluri and Ryzin, page 61. (See also errata, there is a small mistake in the equation). The recursion is as follows:

$V_t(x)=V_{t+1}(x) + \sum\limits_{j=1}^n \lambda_j(t)(p_j-\Delta V_{t+1}(x))^+$

Where $V_t(x)$ is the value function of capacity $x=0,1,..,C$ and time $t=1,..,T$, the $\lambda_j(t)$ the probability of an arrival of product $j$ at time $t$ and $\Delta V_{t+1}(x)=V_{t+1}(x)-V_{t+1}(x-1)$, the opportunity cost of having one unit of capacity.

The boundary conditions are $V_{T+1}(x)$=0 for all $x$ and $V_{t}(x)=0$ for $t=1,..,T$.

This is a backwards reduction problem, so we start at $t=T$. Since $V_{T+1}(x)=0$ for all $x$, we have $V_T(x)=0 + \sum\limits_{j=1}^n \lambda_j(t) (p_j-(0-0))= \sum\limits_{j=1}^n \lambda_j(t)p_j$ for all $x>0$.

Working back, at $T-1$:

$V_{T-1}(x)=V_T(x) + \sum\limits_{j=1}^n \lambda_j(t-1) (p_j-(V_T(x)-V_T(x-1)))$

Now, since $V_T(x)=\sum\limits_{j=1}^n \lambda_j(t)p_j$ for all $x$, doesn't this reduce to:

$V_{T-1}(x)=V_T(x) + \sum\limits_{j=1}^n \lambda_j(t-1) (p_j-(0))=V_T(x)+\sum\limits_{j=1}^n \lambda_j(t-1)p_j$

I am fairly sure shouldn't happen - why else include the term in the recursion? However, I've been looking at this problem for the past two weeks now and I just really don't get where I am going wrong.

Any help would be greatly appreciated.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.